Study of heat and momentum transfer to colloidal suspensions in annular closed conduit flow / Shoaib Sadik - Shoaib, Sadik (2020)
With the advancement of science and the rapid growth of industries and the improved lifestyles of people, energy consumption has been increasing. Whereas the exploration of energy remained at a slower pace and the energy reservoirs are extinguishing at a faster rate. High energy consumption is also encouraging environmental pollution and global warming. Considering all these issues, scientists and engineers are desperately exploring highly efficient heat exchangers for the conservation of energy and minimize its losses. The present research has focused on obtaining highly efficient heat exchangers. Lots of research have performed on the improvement of heat exchanger materials, alteration of process parameters, and enhancement of surface areas but there are limited works on exploration and use of high thermal performance heat exchanger liquids. The present research was focused on the synthesis and application of high thermal performance nanofluid for efficient heat exchangers of circular concentric annular flow passage configuration. Aluminium oxide nanoparticle-based suspension fluids of low concentrations (0.025 to 0.1 vol. %) were prepared using probe sonicator and applied in the annular heat exchanger for heat transfer and friction loss analyses. No additives were selected to ensure the environmental protection. There were 3.4 to 17% enhancement in heat transfer coefficient over water alone in the Reynolds number range of 2.4 to 4.8×103. As the annular flow passage in heat transfer applications is common, so the present findings will provide some information to the researchers and support in the design of more efficient heat exchangers.